Women, family, and gender in Islamic law - Tucker, Judith E. (Cambridge, UK ; New York : Cambridge University Press, 2008)
Examines the position of women in Islamic society, and the ways in which the legal system has shaped the family, property rights, space, and sexuality, from classical and medieval times to the present, with case studies that illustrate discrimination and expectations in the culture.
Introduction -- Woman as wife and man as husband : making the marital bargain -- Woman and man as divorced : asserting rights -- Woman and man as legal subjects : managing and testifying -- Woman and man in gendered space : submitting.
Includes bibliographical references (pages 232-243) and index.
Print version record.
Master record variable field(s) change: 650
Keywords: Women (Islamic law); Married women (Islamic law); Divorce (Islamic law); Domestic relations (Islamic law); RELIGION -- Islam -- Law; Divorce (Islamic law); Domestic relations (Islamic law); Married women (Islamic law); Women (Islamic law); Familierecht; Ehescheidungsrecht; Familie; Islam; Eherecht; Frau; Rechtsstellung; Ehescheidung; Familienrecht; Geschlechterrolle; Islamisches Recht; Electronic books